2022
DOI: 10.3389/fcvm.2022.826744
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Non-coding RNAs and Transcription Factors in Calcific Aortic Valve Disease

Abstract: BackgroundCalcific aortic valve disease (CAVD) is one of the most frequently occurring valvular heart diseases among the aging population. Currently, there is no known pharmacological treatment available to delay or reverse CAVD progression. The regulation of gene expression could contribute to the initiation, progression, and treatment of CAVD. Non-coding RNAs (ncRNAs) and transcription factors play essential regulatory roles in gene expression in CAVD; thus, further research is urgently needed.Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 78 publications
(84 reference statements)
1
3
0
Order By: Relevance
“…Another research reported that GZMB mediates IL-8/macrophage inflammatory protein-2 secretion ( 39 ). Further, Guo et al’s study also reported that GZMB was differentially expressed gene in CAVD datasets ( 40 ), which supports our analysis.…”
Section: Discussionsupporting
confidence: 89%
“…Another research reported that GZMB mediates IL-8/macrophage inflammatory protein-2 secretion ( 39 ). Further, Guo et al’s study also reported that GZMB was differentially expressed gene in CAVD datasets ( 40 ), which supports our analysis.…”
Section: Discussionsupporting
confidence: 89%
“…According to Okazaki and Honjo (2007) , Gotsman et al (2007) , Weyand et al (2018) , and Sun et al (2020) , Bu et al (2011) alterations in PD-1 or PD-L1 expression can influence the degree of inflammation and condition of coronary plaques in atherosclerosis. Granzyme B ( GZMB ) is a protease secreted by T cells and NK cells and is known for its pro-apoptotic properties ( Voskoboinik et al, 2015 ; Guo et al, 2022 ). Previous by qPCR and immunohistochemistry data confirmed that GZMB expression was higher in calcified aortic valve tissues than in control valves ( Ohukainen et al, 2015 ; Guo et al, 2022 ), which is in line with our results, where we found correlations between GZMB expression and calcification grade in coronary and tibial artery.…”
Section: Discussionmentioning
confidence: 99%
“…Granzyme B ( GZMB ) is a protease secreted by T cells and NK cells and is known for its pro-apoptotic properties ( Voskoboinik et al, 2015 ; Guo et al, 2022 ). Previous by qPCR and immunohistochemistry data confirmed that GZMB expression was higher in calcified aortic valve tissues than in control valves ( Ohukainen et al, 2015 ; Guo et al, 2022 ), which is in line with our results, where we found correlations between GZMB expression and calcification grade in coronary and tibial artery. Furthermore, we have not found signs of adaptive immune response deregulation in the blood of the subject with vascular calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, operative resection, chemotherapy, targeted-therapies, and immunotherapies dominate the treatment of CRC ( 27 , 28 ). The selection of therapeutic strategies is determined by each patient’s medical status and the clinical characteristics and phase of the tumor.…”
Section: Discussionmentioning
confidence: 99%